PROBLEM EKSISTENSI TRANSGENDER DI INDONESIA DARI PERSPEKTIF POLITIK KOMUNITARIAN - Lailiy Muthmainnah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2014)
Issue of transgender is rising in the life of Indonesian society. To analyze the issue, I use a philosophical approach of communitarianism politics. This study is a library research with content analysis method and hermeneutics. Result of this study shows that the existence of transgender in Indonesia is closely related to orientation of constructed values in Indonesian society. Indonesia is one country that put heterosexualism as a normative value of society or a form of normativity (hetero-normativity). Therefore, identity of gender should be parallel with sexual identity, there is no third choice. This condition is embedded in Indonesian society as well as an assumption of communitarianism which says that orientation of individual values is based on values of his/her society.Then, it will determine the individual existence in his/her society.